1996
DOI: 10.1139/v96-093
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical exammation of the Diels–Alder reaction of 1,3-butadiene with cyclopentadiene and 2H-phosphole

Abstract: All Diels-Alder reactions between 1,3-butadiene and cyclopentadiene or 2H-phosphole have been examined at the MP4SDQJ6-3 lG*//HF/6-31G* level. There is remarkable similarity between the two systems. The thermodynamic product is the bicyclo[4.2.0]nonadiene while the kinetic product is the norbornene product. There is a slight kinetic preference for the endo addition and for the butadiene to be in the s-trans conformation. Except for the case where butadiene is the diene component and addition is endo, the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
(19 reference statements)
2
12
1
Order By: Relevance
“…Among the chemistries of five-membered heterocyclic compounds, that of phospholes is rather limited compared with those of pyrrole, furan, and thiophene. , However, soon after the discovery and unambiguous characterization of parent and substituted analogues, , the chemistry of phosphole has gained momentum, with notable contributions from Mathey's group . Exploration of the structure, stability, aromaticity, and reactivity of phospholes is intrinsically interesting due to their unique nature and has generated meaningful interplay between theoretical and experimental studies. Although both 1 H - and 2 H -phospholes were independently characterized, ,, 3 H -phosphole is still elusive and is available only in the benzo-fused form, denoted as 3 H -phosphaindene . Phospholes and their Diels−Alder adducts exhibit novel modes of binding with transition-metal fragments, and phosphametallocenes have useful catalytic applications in olefin polymerizations. Phospholes containing transition-metal fragments were also found to have potential applications in homogeneous catalysis such as hydrogenation, carbonylation, and hydroformylation reactions as well as in asymmetric synthesis …”
Section: Introductionmentioning
confidence: 99%
“…Among the chemistries of five-membered heterocyclic compounds, that of phospholes is rather limited compared with those of pyrrole, furan, and thiophene. , However, soon after the discovery and unambiguous characterization of parent and substituted analogues, , the chemistry of phosphole has gained momentum, with notable contributions from Mathey's group . Exploration of the structure, stability, aromaticity, and reactivity of phospholes is intrinsically interesting due to their unique nature and has generated meaningful interplay between theoretical and experimental studies. Although both 1 H - and 2 H -phospholes were independently characterized, ,, 3 H -phosphole is still elusive and is available only in the benzo-fused form, denoted as 3 H -phosphaindene . Phospholes and their Diels−Alder adducts exhibit novel modes of binding with transition-metal fragments, and phosphametallocenes have useful catalytic applications in olefin polymerizations. Phospholes containing transition-metal fragments were also found to have potential applications in homogeneous catalysis such as hydrogenation, carbonylation, and hydroformylation reactions as well as in asymmetric synthesis …”
Section: Introductionmentioning
confidence: 99%
“…Much progress has been made recently in the preparation of phosphaalkynes, and these species are now readily accessible suggested that the phosphorus analogue (reaction 2) may be easier to observe. We report here a high-level ab initio calculation comparing the energetics of these two reactions.…”
mentioning
confidence: 99%
“…Similarly, the structure of TS2 is in accord with previous studies, with the forming C···C distance a bit shorter than usual. The forming C···P distance of 2.514 Å is typical for pericyclic reactions. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, significant effort has been made to explore the ene chemistry of thio-carbonyl compounds. Since we have been interested in the pericyclic reactions of heteroatomic systems, we decided to explore the nature of the mechanism of this reaction. In this paper, we report ab initio calculations on the thio-ene reaction, exploring the effect of substitution of the enophile.…”
mentioning
confidence: 99%